Did a Successful Fight against the COVID-19 Pandemic Come at a Cost? Impacts of the Outbreak on Employment Outcomes in Vietnam - Hai-Anh Dang; Cuong Viet Nguyen (Institute of Labor Economics (IZA), 2020)
Vietnam is widely praised for its successful fight against the COVID-19 pandemic. The country has had an extremely low mortality rate of 35 deaths to date (out of a population of approximately 100 million) and currently has no community transmission. We offer the first study that examines the effects of the COVID-19-induced lockdown on various employment outcomes for Vietnam. We employ difference-in-differences econometric models to estimate the causal effects of the lockdown, using rich individual-level data from the quarterly Labor Force Surveys. We find that the lockdown increases the unemployment rate, the temporary layoff rate, and decreases the quality of employment. It also reduces workers' numbers of working hours and their monthly incomes and wages. Our estimation results remain robust to different model specifications and estimation samples. Further heterogeneity analysis suggests that the effects vary across education levels and occupation sectors but are similar across regions or provinces with different lockdown durations.
Keywords: E24; I30; J21; O12; 330; COVID-19; employment; income loss; differences-in-differences; Vietnam